Effects of uracil calculi on cell growth and apoptosis in the BBN-initiated Wistar rat urinary bladder mucosa - de Oliveira, S. V.; de Camargo, JLV; Cardoso, P. R.; Padovani, Carlos Roberto [UNESP]; Fukushima, S. (Wiley-Blackwell, 1999)
The different potential of initiated and non-initiated urinary bladder mucosa (UBM) to develop neoplasia was quantitatively evaluated in the male Wistar rat. Initiation of carcinogenesis was accomplished with N-butyl-N- (4-hydroxybutyl) -nitrosamine (BBN). Stimuli for cell proliferation and apoptosis were obtained by exposure followed by withdrawal of 3% Uracil in the diet. The proliferation index (PI) was estimated in UBM immunostained for the proliferating nuclear cell antigen (PCNA). The apoptotic index (AI) and the density of papillary/nodular hyperplasia (PNH) were estimated in hematoxilin-eosin stained sections. PNH was the main proliferative response to the mechanical irritation by uracil, irrespective of previous initiation with BBN. Uracil exposure induced higher PI and PNH density in the initiated rats. After uracil withdrawal, there was a significant increase of the AI in both uracil-treated groups, which correlated well to the respective PNH density. However, at the end of the experiment, PNH incidence and density were significantly higher in the BBN-initiated mucosa, which also presented 18% incidence of papillomas and 27% of carcinomas. Therefore, under prolonged uracil calculi trauma, the UBM of BBN-initiated Wistar rats gives rise to epithelial proliferative lesions that progress to neoplasia through acquired resistance to apoptosis. (C) 1999 Wiley-Liss, Inc.
Keywords: cell proliferation; two-step carcinogenesis; urothelial neoplasia; urinary calculi; Wistar rat